Rice TUTOU1 Encodes a Suppressor of cAMP Receptor-Like Protein That Is Important for Actin Organization and Panicle Development. Issue 2 (4th August 2015) - Bai, Jiaoteng; Zhu, Xudong; Wang, Qing; Zhang, Jian; Chen, Hongqi; Dong, Guojun; Zhu, Lei; Zheng, Huakun; Xie, Qingjun; Nian, Jinqiang; Chen, Fan; Fu, Ying; et al.
Abstract : An actin nucleation protein affects rice panicle development as well as root growth. Abstract: Panicle development, a key event in rice ( Oryza sativa ) reproduction and a critical determinant of grain yield, forms a branched structure containing multiple spikelets. Genetic and environmental factors can perturb panicle development, causing panicles to degenerate and producing characteristic whitish, small spikelets with severely reduced fertility and yield; however, little is known about the molecular basis of the formation of degenerating panicles in rice. Here, we report the identification and characterization of the rice panicle degenerative mutant tutou1 (tut1), which shows severe defects in panicle development. The tut1 also shows a pleiotropic phenotype, characterized by short roots, reduced plant height, and abnormal development of anthers and pollen grains. Molecular genetic studies revealed that TUT1 encodes a suppressor of cAMP receptor/Wiskott-Aldrich syndrome protein family verprolin-homologous (SCAR/WAVE)-like protein. We found that TUT1 contains conserved functional domains found in eukaryotic SCAR/WAVE proteins, and was able to activate Actin-related protein2/3 to promote actin nucleation and polymerization in vitro. Consistently, tut1 mutants show defects in the arrangement of actin filaments in trichome. These results indicate that TUT1 is a functional SCAR/WAVE protein and plays an important role in panicle development.